2020
DOI: 10.3390/ani10040727
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Heavy Metal Content in Feed, Litter, Meat, Meat Products, Liver, and Table Eggs of Chickens

Abstract: We assessed the concentrations of Fe, Cu, Zn, Mn, Se, Co, Cr, Pb, Cd, and Ni in chicken meat and meat products, feed, and litter, as well as laying hens’ eggs, feed and litter to monitor the quality of products on the market and their safety for human consumption as judged by recommended daily allowance (RDA) and tolerable upper levels. Samples were chosen as the most popular poultry products in Saudi Arabia. A total of 45 broiler samples of frozen or fresh meat, liver, burger, or frankfurter were chosen from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
65
9
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 75 publications
7
65
9
6
Order By: Relevance
“…By comparison with the results of laying performance and egg quality, it was implied that the basal diet with 0.15 mg Se/kg was adequate for productive performance but not for antioxidant balance. In addition, it was acknowledged that Se is key to the maintenance of various physiological and biochemical functions within a small amount, while an excessive dose may lead to harmful effects (41). The Se supplementation at 0.15 and 0.25 mg/kg diet via Se yeast improves the antioxidant balance of the laying ducks in our study, and the average value of Se supplementation level from Se yeast was 0.19 mg/kg for optimum antioxidant balance.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…By comparison with the results of laying performance and egg quality, it was implied that the basal diet with 0.15 mg Se/kg was adequate for productive performance but not for antioxidant balance. In addition, it was acknowledged that Se is key to the maintenance of various physiological and biochemical functions within a small amount, while an excessive dose may lead to harmful effects (41). The Se supplementation at 0.15 and 0.25 mg/kg diet via Se yeast improves the antioxidant balance of the laying ducks in our study, and the average value of Se supplementation level from Se yeast was 0.19 mg/kg for optimum antioxidant balance.…”
Section: Discussionmentioning
confidence: 51%
“…So far, one of the effective ways to improve Se intake is to consume some functional food, such as Se-enriched egg, meat, and milk products (10,27,62). However, the Se content in ordinary eggs collected from the retail market is under detectable levels (41,63). Many studies have demonstrated that organic Se supplementation of the diets of laying hens translates into greater Se content and Se deposition efficiency in their eggs compared to using inorganic Se (16,17,64,65).…”
Section: Discussionmentioning
confidence: 99%
“…Se is also part of the deiodinase enzyme essential for the activation of the thyroid hormone ( 97 , 101 , 102 ). The main functions of selenoproteins are control of redox of biochemical function, antioxidant balance systems, thyroid hormone anabolism and catabolism ( 106 ), anticancer protection ( 108 ), and immune function booster ( 117 , 118 ). Hence, Se-enhanced animal products can improve animal immunity, prevent diseases caused by Se deficiency, and enrich general health ( 97 , 101 , 102 ).…”
Section: Changes In Political and Social Conditions And Consumer Percmentioning
confidence: 99%
“…Hence, Se-enhanced animal products can improve animal immunity, prevent diseases caused by Se deficiency, and enrich general health ( 97 , 101 , 102 ). Se fortification can enhance the antioxidant balance of animals and improve product quality and animal performance ( 119 121 ), but excess Se may hurt the environment ( 108 , 117 ).…”
Section: Changes In Political and Social Conditions And Consumer Percmentioning
confidence: 99%
“…Birds receiving diets containing reduced levels of trace elements had diminished excretions of Mn and Zn throughout the entire period (p < .01) and droppings of such broilers, fed with this feed mixtures, were not loading the environment too much with trace elements residues. Also Korish and Attia (2020) assessed the concentrations of Fe, Cu, Zn, Mn, Se, Co, Cr, Pb, Cd, and Ni in chicken meat and meat products, feed, and litter, as well as laying hens' eggs, feed and litter to monitor the quality of products on the market and their safety for human consumption and their results indicated that there were significant levels of most of the trace elements and heavy metals in the different meat sources.…”
Section: Discussionmentioning
confidence: 99%